Preserving Data Privacy without Secure Channel (International Journal of Engineering and Computer Science, 2016)
The main objective is to preserve data privacy during communication. In this paper, we show how external aggregators or multiple parties use algebraic statistics over their private data without exploiting data privacy assuming all channels and communications are open to eavesdropping attacks. Firstly, we propose many protocols that guarantee data privacy. Later we propose advanced protocols that tolerate maximum of k passive adversaries who do not try to modify the computation.